Effects of plyometric jump training on the reactive strength index in healthy individuals across the lifespan: a systematic review with meta-analysis - Ramirez-Campillo, R.; Thapa, R. K.; Afonso, J.; Perez-Castilla, A.; Bishop, C.; Byrne, P. J.; Granacher, U. (Sports Medicine, 2023)
Background: The reactive strength index (RSI) is meaningfully associated with independent markers of athletic (e.g., linear sprint speed) and neuromuscular performance [e.g., stretch-shortening cycle (SSC)]. Plyometric jump training (PJT) is particularly suitable to improve the RSI due to exercises performed in the SSC. However, no literature review has attempted to meta-analyse the large number of studies regarding the potential effects of PJT on the RSI in healthy individuals across the lifespan. Objective: The aim of this systematic review with meta-analysis was to examine the effects of PJT on the RSI of healthy individuals across the lifespan compared with active/specific-active controls. Methods: Three electronic databases (PubMed, Scopus, Web of Science) were searched up to May 2022. According to the PICOS approach, the eligibility criteria were: (1) healthy participants, (2) PJT interventions of = 3 weeks, (3) active (e.g., athletes involved in standard training) and specific-active (e.g., individuals using heavy resistance training) control group(s), (4) a measure of jump-based RSI pre-post training, and (5) controlled studies with multi-groups in randomised and non-randomised designs. The Physiotherapy Evidence Database (PEDro) scale was used to assess the risk of bias. The random-effects model was used to compute the meta-analyses, reporting Hedges` g effect sizes (ES) with 95% confidence intervals (95% CIs). Statistical significance was set at p = 0.05. Subgroup analyses were performed (chronological age; PJT duration, frequency, number of sessions, total number of jumps; randomization). A meta-regression was conducted to verify if PJT frequency, duration, and total number of sessions predicted the effects of PJT on the RSI. Certainty or confidence in the body of evidence was assessed using Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Potential adverse health effects derived from PJT were researched and reported. Results: Sixty-one articles were meta-analysed, with a median PEDro score of 6.0, a low risk of bias and good methodological quality, comprising 2576 participants with an age range of 8.1-73.1 years (males, ~ 78%; aged under 18 years, ~ 60%); 42 studies included participants with a sport background (e.g., soccer, runners). The PJT duration ranged from 4 to 96 weeks, with one to three weekly exercise sessions. The RSI testing protocols involved the use of contact mats (n = 42) and force platforms (n = 19). Most studies reported RSI as mm/ms (n = 25 studies) from drop jump analysis (n = 47 studies). In general, PJT groups improved RSI compared to controls: ES = 0.54, 95% CI 0.46-0.62, p < 0.001. Training-induced RSI changes were greater (p = 0.023) for adults [i.e., age = 18 years (group mean)] compared with youth. PJT was more effective with a duration of > 7 weeks versus = 7 weeks, > 14 total PJT sessions versus = 14 sessions, and three weekly sessions versus < three sessions (p = 0.027-0.060). Similar RSI improvements were noted after = 1080 versus > 1080 total jumps, and for non-randomised versus randomised studies. Heterogeneity (I2) was low (0.0-22.2%) in nine analyses and moderate in three analyses (29.1-58.1%). According to the meta-regression, none of the analysed training variables explained the effects of PJT on RSI (p = 0.714-0.984, R2 = 0.0). The certainty of the evidence was moderate for the main analysis, and low-to-moderate across the moderator analyses. Most studies did not report soreness, pain, injury or related adverse effects related to PJT. Conclusions: The effects of PJT on the RSI were greater compared with active/specific-active controls, including traditional sport-specific training as well as alternative training interventions (e.g., high-load slow-speed resistance training). This conclusion is derived from 61 articles with low risk of bias (good methodological quality), low heterogeneity, and moderate certainty of evidence, comprising 2576 participants. PJT-related improvements on RSI were greater for adults versus youths, after > 7 training weeks versus = 7 weeks, with > 14 total PJT versus = 14 sessions, and with three versus < three weekly sessions.